2014
DOI: 10.1136/bmjdrc-2014-000026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3supplementation on glycated hemoglobin (HbA1c), fructosamine, serum lipids, and body mass index: a randomized, double-blinded, placebo-controlled trial among healthy immigrants living in Norway

Abstract: ObjectiveDespite the suggested role of vitamin D in the prevention of diabetes and cardiovascular disease or its risk factors, the evidence is not consistent and there is a paucity of randomized controlled trials in this field. We aimed to investigate the effect of 16-week daily vitamin D3 supplementation on glycated hemoglobin (HbA1c), fructosamine, body mass index (BMI), and serum lipids.DesignDouble-blind, randomized, placebo-controlled trial.SettingImmigrant community centers in Oslo, Norway.Participants25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…We found no association between using of Vit D and serum Hb A 1c , however different results were reported in other studies, for example, in Madar et al 16-week administration of Vit D 3 to healthy individuals with low Vit D status showed no improvement for HbA 1c (26). Likewise, Ahmadi et al reported no significant difference based on HbA 1C in both case and control groups (21).…”
Section: Discussioncontrasting
confidence: 82%
“…We found no association between using of Vit D and serum Hb A 1c , however different results were reported in other studies, for example, in Madar et al 16-week administration of Vit D 3 to healthy individuals with low Vit D status showed no improvement for HbA 1c (26). Likewise, Ahmadi et al reported no significant difference based on HbA 1C in both case and control groups (21).…”
Section: Discussioncontrasting
confidence: 82%
“…Cross-sectional studies overwhelmingly demonstrated the existence of an inverse association of circulating 25-hydroxyvitamin D [25(OH)D], the nutritional biomarker for vitamin D status, with HbA 1c concentration, both in patient groups [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and community samples [ 17 , 22 , 23 ], though a few studies failed to confirm this association [ 13 , 24 ]. Randomized controlled trials (RTCs) studying the effect of vitamin D supplementation regimens have been less consistent, with the majority not showing a lowering in HbA 1c values [ 7 , 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and a minority showing a reduction in HbA 1c concentration [ 33 , 34 , 35 ]. These RCTs typically focused on patient groups with T2D or at risk for T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, vitamin D-fortified foods need to be considered as a possible strategy to facilitate population intake of the RNI. Furthermore, a few recent studies have used higher doses of vitamin D in their intervention trials (33)(34)(35) , which also showed no associations of vitamin D intake with CVD risk. The strength of the CAPS is the long (over 20 years) follow-up period.…”
Section: Discussionmentioning
confidence: 99%